Peranan Pemerintah Dalam Meningkatkan Produk Indikasi Geografis di Indonesia - Sugih Ayu Pratitis (Universitas Harapan Medan, 2021)
In addition to the role of government entrepreneurs optimally, proper preparation of human resources is needed. The right human resources will greatly assist in the development of potential geographic indications in Indonesia. As a field of law that is not yet popular among practitioners, academics, and the public, counseling about geographical indications is very important. Academics do not understand and understand about IPR and moreover about geographical indications. Because geographical indication is a new thing in Indonesia. Understanding of geographical indications is new in Indonesia. Understanding of geographical indications requires socialization to prevent violations of these geographical indications. The government's role in increasing geographical indication products in Indonesia is through the government's efforts to increase the utilization of geographical indication products in Indonesia, namely by maximizing the utilization of geographical indications where in this case the government is represented by the Ministry of Industry and Trade (Depperindag), namely by providing guidance and conducting searches and collecting data and forming cross-departmental collaborations that are relevant nationally and internationally. To resolve the unlawful abuse of geographical indications in Indonesia, the government can make its own provisions in the Geographical Indication Law or add articles in the trademark law which explicitly regulates the legal protection of geographical indications which refers to the Monopoly and competition Law. unhealthy business, for fake and misleading goods.